Atorvastatin restricts HIV replication in CD4+ T cells by upregulation of p21 - Elahi, Shokrollah; Weiss, Robert H.; Merani, Shahzma (AIDS (London), 2016)
OBJECTIVE:Antigen persistence due to HIV is a major source of inflammation and substantial immune activation, both of which are linked to accelerated aging. This illustrates the need to reduce immune activation in these patients and subsequently decrease the risk of cardiovascular diseases and other non-AIDS-defining comorbidities. METHODS:CD4 T cells were infected with HIV-1 isolates in the presence or absence of atorvastatin (0.25 to 1 μg/ml) for 24–48 h. Atorvastatin-induced anti-inflammatory functions and anti-viral replication were measured in vitro. RESULTS:Atorvastatin, a lipid-lowering medication, exerted a broad spectrum of anti-inflammatory functions by reducing T-cell immune activation markers (e.g. CD38, HLA-DR and Ki67), lowering HIV-1 co-receptor CCR-5, and decreasing proliferative capabilities of CD4 T cells in vitro. In contrast, atorvastatin expanded regulatory T cells (Tregs) and upregulated the expression of T-cell immunoglobulin and ITIM domain (TIGIT), which enhanced the suppressive activity of Tregs. Furthermore, atorvastatin upregulated the cyclin-dependent kinase inhibitor p21, which is also known as cip-1 and waf-1, in the CD4 T cells. Upregulation of p21 in CD4 T cells rendered them less susceptible to HIV-1 infection and replication whereas siRNA-mediated p21 depletion and/or p21 selective inhibitor rescued viral replication. Interestingly, atorvastatin reduced HIV infection in both rested and phytohemagglutinin-activated CD4 T cells in vitro. Finally, atorvastatin mediated p21 upregulation occurred via mevalonate pathway, but independent of p53. CONCLUSION:The results demonstrate a novel mechanism by which atorvastatin induced resistance of CD4 T cells to HIV-1 infection via p21 upregulation and suggest that statins may hold particular promise for some HIV-infected individuals.